Differences in Anemia Status and Knowledge of Adolescent Women Before and After Counseling and Administration of Fe Tablets - Nuburi, Dorci; Setyarini, Anis; Iriyanti, Sri; Budi Astuti, Nia (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Adolescent girls are at risk of suffering from anemia, because during this period there is an increase in iron requirements due to growth and menstruation. This study aimed to determine differences in anemia status and knowledge of young women before and after counseling and giving blood supplement tablets. The research was conducted from March 24 to April 24 2022 at SMPN 4 Arso, Keerom Regency. The research method used a quasi-experimental research type with a One Pretest-Posttest Group Design. Determination of samples based on certain considerations. The sampling technique used is purposive sampling. The data collection method uses sample identity data, knowledge data and nutritional anemia data obtained by measuring the sample's hemoglobin levels. Analysis uses the Wilcoxon Test. It is known that the statistical test results show Asymp.sig = 0.000 where the Asymp.sig value 0.05. There was a difference in increasing the knowledge of young women using counseling and action posters. Anemia status before intervention was found in 18 samples (100%) with anemia status before intervention. Meanwhile, anemia status after intervention was 3 samples (16.66%). This shows that there was a difference in the anemia status of young women before and after giving blood supplement tablets. The study concluded that there were differences in knowledge and anemia status after the intervention of giving Fe tablets and education using action posters. Suggestions for further research could consider other factors that can influence knowledge and anemia status, such as diet and physical activity.